2017
DOI: 10.1111/geb.12699
|View full text |Cite
|
Sign up to set email alerts
|

Are the radiations of temperate lineages in tropical alpine ecosystems pre‐adapted?

Abstract: Aim Tropical mountains around the world harbour an extraordinarily rich pool of plant species and are hotspots of biodiversity. Climatically, they can be zoned into montane climates at mid‐altitudes and tropical alpine climates above the tree line. Around half of the tropical alpine species belong to plant lineages with a temperate ancestry, although these regions are often geographically distant. We test the hypothesis that these temperate lineages are pre‐adapted to the tropical alpine climate. Location New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 57 publications
(74 reference statements)
0
30
0
1
Order By: Relevance
“…). This is a result of reliance on mean heights as a proxy for growth form (Notes S1) and the similar disparity of growth forms in a woody North America clade (Nürk et al ., ). Second, as indicated earlier (see the Materials and Methods section), Lupinus species were coded as annual or perennial (rather than herbaceous or woody), because many North American species are herbaceous perennials.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…). This is a result of reliance on mean heights as a proxy for growth form (Notes S1) and the similar disparity of growth forms in a woody North America clade (Nürk et al ., ). Second, as indicated earlier (see the Materials and Methods section), Lupinus species were coded as annual or perennial (rather than herbaceous or woody), because many North American species are herbaceous perennials.…”
Section: Discussionmentioning
confidence: 97%
“…(Asteraceae), which includes the Hawaiian silversword alliance and tarweeds from California and the California islands (Channel Islands, Guadalupe, and San Benito Islands), hereafter silverswords–tarweeds, plus two well‐studied Andean sky island radiations, Hypericum L. (Hypericaceae) and Lupinus L. (Fabaceae). For each group we used the best sampled time tree (C. S. Drummond et al ., ; Nürk et al ., ) or reconstructed a phylogeny using published sequence data and estimated divergence times under relevant age constraints using an uncorrelated lognormal relaxed‐clock model in Beast v.1.8 (A. J. Drummond et al . (); for details about sampled taxa, DNA sequence loci, and fossil constraints see Supporting Information Table S1; Methods S1).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting map delineates 12 percent of global land area as mountainous; this includes the rugged parts of the Tibetan plateau and the Andean altiplano, both above 2500 masl, but not significant areas of low-elevation mountains with elevations from 300 to 1000 masl identified by Kapos et al (2000) -though it does include some areas below 300 masl. The underlying database forms the foundation for a global inventory of mountain areas and their biodiversity (http://www.mountainbiodiversity.org) which is being used as the basis for research (e.g., Nürk et al 2018).…”
Section: Global Experiencesmentioning
confidence: 99%
“…Hence, forces in addition to variations in environmental parameters, such as natural selection or genetic drift, are prompting the radiation of these hummingbirds. Previous studies demonstrated the utility of niche modelling techniques to assess conservation, ecological, taxonomic biogeographic and evolutionary questions in the tropical Andes, including plants (Sanín et al 2016, Zutta and Rundel 2017, Nürk et al 2018, Oleas et al 2019, Testo et al 2019), insects (Moo-Llanes et al 2017, Scattolini et al 2018), amphibians (Ramos Pallares et al 2018, reptiles (Aguilar et al 2016), mammals (Ramoni-Perazzi et al 2012, Gutiérrez et al 2015, Gerstner et al 2018, Bennett et al 2019) and birds (Cadena and Cuervo 2010, Freile et al 2010, Jiguet et al 2010, Thomassen et al 2010, Velásquez-Tibatá et al 2013, Ramirez-Villegas et al 2014, Avendaño and Donegan 2015, Ramoni-Perazzi et al 2017. Thus, the results presented here are based on a solid background with regards to the applicability of niche modelling procedures in Neotropical environmental complex regions.…”
Section: Discussionmentioning
confidence: 99%